Knowledge management in libraries: concepts, tools and approaches - Nazim, Mohammad. ; Mukherjee, Bhaskar. (Chandos Publishing is an imprint of Elsevier, 2020)
There is an increasing recognition of the value of knowledge and information to individuals, organizations and communities. Individuals are more adept at identifying, locating, interpreting and using knowledge. As knowledge has become a central productive and strategic asset, the success of all types of organizations is increasingly depend on their ability to acquire, create, store, share and utilize knowledge. That is why, developing procedures and routines to optimize the acquisition, creation, protection and sharing of knowledge and information in the organizations has become one of the most important activities. Knowledge Management in Libraries: Concepts, tools and Approaches, is an analysis of the concepts of Knowledge Management (KM) that prevails among the Library and Information Science (LIS) community. Thus, the proposed book will explore KM from the perspective of the LIS professionals. Furthermore, unlike most books on KM, which address it almost exclusively in the context of a firm or an organization to help gain a competitive advantage, this book looks at KM in the context of not for profit organizations such as libraries. Describes the theory and approaches of knowledge management in the context of librarianship. Seeks to identify and explain the principles that underlie the different processes of knowledge management. Combines the theoretical and practical perspectives of knowledge management. Provides a comprehensive and methodological approach to support librarians and information science professionals in the implementation of knowledge management in libraries and information centers. Proposes a knowledge management model for libraries and information centers which may be used as a guide for implementing knowledge management. Incorporates illustrations where necessary for clear understanding of the concepts.